Abraham Lincoln - Latham, Frank Brown (New York F. Watts, 1968)
A biography of the sixteenth President with emphasis on the Civil War years.
Keywords: Lincoln, Abraham -- 1809-1865.; Presidents; United States -- History -- Civil War, 1861-1865.